Differentiated Instruction in In-Person Classes and the Enhancement of Analytical Thinking Skills of Grade 7 Students in Araling Panlipunan - Emralino, Mark Paul I. (Future Science / FSH-PH Publications, 2023)
Differentiated instruction aims to meet the individual differences and learning styles of students through different classroom management strategies. This research study investigated the utilization of differentiated instruction and the enhancement of analytical thinking skills of Grade 7 students in Araling Panlipunan in Col. Lauro D. Dizon Memorial Integrated High School. This research study employed a quasi-experimental research design specifically a Pretest-Posttest Nonequivalent Groups Design. Two regular sections consisting of eighty (80) heterogeneously-grouped learners comprised the experimental group and control group. This study utilized a homogenous convenience sampling wherein two (2) equal groups of learners from two heterogenous sections were identified. The researcher constructed three self-made semi-detailed lesson plans to cover the first three weeks of third grading period incorporated with differentiated instruction approach. Survey questionnaire and pre-test and post-test were utilized. Frequency and percentage were utilized. Mean and standard deviation was also utilized. Pearson-moment correlation was used in measuring the perception of the respondents. Furthermore, Paired Samples T-test were utilized for the pre-test and post-test instrument. Findings of the study revealed that the students perceived the use of differentiated instruction as to content, process, product, and affect/environment as